Evolution of product packaging form from the perspective of media evolution and artistic philosophy - Zhen Chen; Yu He (Trans/Form/Ação)
The purpose of this article is to discuss the evolution of commodity packaging forms from the perspective of media evolution and art philosophy. Firstly, the historical evolution of commodity packaging, in the process of media evolution, is analyzed, from handmade to digital design, revealing the changes of packaging media in different periods. Subsequently, from the perspective of art philosophy, the article analyzed the connotation of commodity packaging, as an art form, and discussed the use of artistic elements in packaging design and its role in conveying emotions and concepts. In this context, this paper takes the evolution of media and art philosophy as the entry point to analyze the evolution of commodity packaging forms.